Gender and Migration Gendered Dynamics of Male Labour Migration: Assessing Impacts on Women’s Empowerment in the Nepalese Context - Singh, Mahima (Academic View, Journal of TUTA Tri-Chandra Campus Unit, 2023)
This article offers a brief summary of the changes in the lives of Nepalese women due to the increasing trend of men migrating abroad for work in Nepal. Primarily centred on the economic benefits derived from remittances, shifts in intra-household power dynamics, and an exploration of women’s roles as household leaders, financial managers, and single parents, the article sheds light on their experiences in a society historically limiting their freedom. However, it tends to overlook changes in intra-household power dynamics and the impact of the predominantly male nature of Nepalese migration on women’s lives. The analysis draws insights from secondary data and literature reviews. The study’s outcomes may contribute to a gendered understanding of migration consequences, empowering women with awareness to navigate challenges arising from men’s migration. A review of various literary works suggests that male migration both supports and hinders women’s empowerment. While women gain opportunities such as decision-making, mobility, and assuming household leadership, they also bear the burden of traditionally male responsibilities, with left-behind women living with in-laws experiencing limited freedom compared to those without such constraints.